Not just skin deep: A case report of multiple endocrine neoplasia type 1 - S M Simi; Beena Narayanan; G Nandakumar (Wolters Kluwer Medknow Publications, 2012)
Multiple endrocrine neoplasia (MEN) type 1 is characterized by mainly a triad of pancreatic, pituitary and parathyroid involvement. This is a case report of a 41-year-old male in whom recognition of collagenoma and gingival papule led to the identification of MEN type 1. Often the recognition of such dermatological manifestations help in the presymptomatic diagnosis of complex syndromes.